Distributional impact of the American Recovery and Reinvestment Act: a microsimulation approach - Ajit Zacharias; Thomas Masterson; Kijong Kim (Levy Economics Institute of Bard College, 2009)
Over the last two decades, those at the bottom of the income scale have seen their incomes stagnate, while those at the top have seen theirs skyrocket. Without intervention, the recession that began in December 2007 was likely to exacerbate this trend. Will the American Recovery and Reinvestment Act of 2009 (ARRA) be able to keep the situation from getting worse for those at the bottom of the income scale? Will ARRA reverse the upward trend in inequality that we have seen in the recent past? We employ a microsimulation of ARRA to address these questions. We find that, despite a large amount of job creation, ARRA is likely to have little impact on overall income inequality, or on the income gaps between relatively advantaged and disadvantaged groups.
Keywords: D31; D63; E62; 330; Income distribution; inequality; job creation; American Recovery and Reinvestment Act; policy impacts